Critical issues in psychotherapy translating new ideas into practice - Slife, Brent D.; Williams, Richard N., 1950-; Barlow, Sally H.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2001)
This volume evaluates the theory and practice of new and existing models in psychotherapy. It includes the topics individualism, spirituality, mainstream theories, empirically validated treatments, multiculturalism and managed care.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychotherapy; Electronic books